An assessment of the role of government health related policies in improving the oral health status of Nigerians - A. A. Adeniyi; E. O. Ogunbodede; M. O. Braimoh (Nigerian Dental Association, 2012)
Achieving good oral health is now considered an important component of good health for any population and the inclusion of an oral health component in national health policies is a good strategy for promoting oral health. This paper sought to examine the existing health-related policies of the Nigerian government in order to determine the position accorded oral health within the policy framework and to determine the role of these policies in improving the oral health status of Nigerians. A detailed search of electronic sources and Nigerian government documents to identify the major health related policies of the government in the last decade was conducted. The policies identified and analysed were the Millennium Development Goals (MDG's), Vision 20:2020, National Economic Empowerment and Development strategy (NEEDS), the seven point agenda and the primary health care policy. The analysis from this report indicates an exclusion of oral health from the framework of most of the policies designed by the Nigerian government. The most important barrier identified for excluding oral health is the inability of the oral health workforce to influence the policy process in Nigeria since policymaking is largely a political issue. Oral healthcare professionals in Nigeria need to be actively engaged in the politics of policymaking in order to promote the inclusion of oral health in the health related policies of government. This should stimulate positive action concerning oral health in the Nigerian polity.